2021
DOI: 10.1002/pa.2603
|View full text |Cite
|
Sign up to set email alerts
|

Role of fiscal policy in energy efficiency and CO2 emission nexus: An investigation of belt and road region

Abstract: Belt and road initiative (BRI) contains the transport, construction, and energy-related projects to push the wheel of economic development of BRI's participant at the cost of ecological consequences. These sectors are highly energy-intensive and upsurge the CO 2 emission. Energy efficiency and renewable energy are considered two essential solutions to control CO 2 emissions. Energy efficiency is proficient in yielding energy and demand savings that can relocate the electricity generation from primary energy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…As discussed in previous sections, energy is one of the most important factors in environmental degradation and the use of inefficient and non-renewable energy use is putting a considerable population at risk of different brain, heart, and respiratory diseases. Renewable energy production, consumption, and energy-efficient technologies in the energy sector can play an essential role in addressing climate change (Akbar et al 2021b), ultimately improving health indicators. Previous studies such as Weimin et al (2021), Chishti et al (2021) concluded that renewable energy consumption improves environmental quality by reducing CO 2 emissions and shown a negative association between energy efficiency and environmental pollution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed in previous sections, energy is one of the most important factors in environmental degradation and the use of inefficient and non-renewable energy use is putting a considerable population at risk of different brain, heart, and respiratory diseases. Renewable energy production, consumption, and energy-efficient technologies in the energy sector can play an essential role in addressing climate change (Akbar et al 2021b), ultimately improving health indicators. Previous studies such as Weimin et al (2021), Chishti et al (2021) concluded that renewable energy consumption improves environmental quality by reducing CO 2 emissions and shown a negative association between energy efficiency and environmental pollution.…”
Section: Discussionmentioning
confidence: 99%
“…The atmospheric half-life of NOx is 3 to 5 h (Boon and Marletta 2006), SO 2 is 6 to 1 day (Brimblecombe1996), and almost 27 years of CO 2 . Also, CO 2 emissions are widely used by previous researchers (Akbar et al 2021a, b;Khan et al 2020a, b;Xinmin et al 2020) (Akbar et al 2021b;Hafeez et al 2018;Khan et al 2020a, b;Xinmin et al 2020). GDP per unit of energy use has been used for energy efficiency (Akbar et al 2021b;Malinauskaite et al 2019;Nasir et al 2021).…”
Section: Data and Variables Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the panel data of 69 BRI countries from 2000 to 2014, Khan et al [42] found that technological innovations, economic growth, and foreign direct investment have a negative impact on renewable energy. Similarly, Akbar et al [43] found that energy efficiency can reduce CO 2 emission; however, FDI and GDP will lead to an increase in CO 2 emission. In addition, Akbar et al [44] also analyzed the transport energy efficiency by taking two years as a pre-and post-BRI case, showing that, after the BRI, there is an increase in economic activity but a decline in transport energy efficiency.…”
Section: Literature Reviewmentioning
confidence: 93%